DEGRADABILIDADE RUMINAL DE DIETAS CONTENDO PALMA FORRAGEIRA ASSOCIADA AO FENO DE LEUCENA PARA RUMINANTES. - ALVES, Fabiana Castro (2018)
The objective of this study was to evaluate the in situ ruminal degradability of diets containing forage palm associated with leucine hay as a source of fiber for ruminants. A randomized block design (fistulated cattle) was used, with three treatments that consisted of diets containing: 65% of forage palm (PF) associated with 35% of leucine hay (FL); 55% PF associated with 45% FL and 45% FP associated with 55% FL, on plots subdivided in incubation times in rumen 3; 6; 12; 24 and 72 hours. There was greater (P < 0.05) soluble fraction (a), potentially degradable (b), potential degradation (DP) and effective (DE) of DM and CP to diets containing 65% PF associated with 35% of FL, however, the SD of DM and CP obtained for all the diets declined as increased pass rate (2, 5 and 8% / hour). Largest potentially degradable fraction of NDF (76.40%) and lower pass rate (3.55% / hour) were observed for a diet containing 65% PF associated with 35% FL. There was an effect (P <0.05) of diets for NDF degradation, with a higher value obtained with a diet containing 65% PF associated with 35% FL (38.89%). There was no effect (P> 0.05) on the interaction of diet x time of incubation for degradation of DM, CP and NDF, however were observed quadratic effect of the incubation time (P < 0.05) on the degradation of these rations constituents. The association of 65% PF with 35% FL increases the in situ ruminal degradability of DM, CP and NDF of diets for ruminants, which justifies the recommendation and use in the feeding of these animals.